1997
DOI: 10.1084/jem.185.11.1909
|View full text |Cite
|
Sign up to set email alerts
|

Human Dendritic Cells Skew Isotype Switching of CD40-activated Naive B Cells towards IgA1 and IgA2

Abstract: Within T cell–rich areas of secondary lymphoid organs, interdigitating dendritic cells recruit antigen-specific T cells that then induce B cells to secrete Igs. This study investigates the possible role(s) of dendritic cells in the regulation of human B cell responses. In the absence of exogenous cytokines, in vitro generated dendritic cells (referred to as Dendritic Langerhans cells, D-Lc) induced surface IgA expression on ∼10% of CD40-activated naive sIgD+ B cells. In the presence of IL-10 and TGF-β, a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(161 citation statements)
references
References 43 publications
4
156
1
Order By: Relevance
“…Follicular dendritic cells, which are present in germinal center regions, produce bioactive TGF-␤1 (10). Recently, it was demonstrated that dendritic cells can promote class switching of naive CD40-triggered human B cells to an IgA phenotype in the presence of IL-10, and that this process is partially dependent on endogenous TGF-␤1 (67). It is has also been reported that TGF-␤1 may cause apoptosis in human B cells isolated from tonsil, preparations that contain germinal center B cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Follicular dendritic cells, which are present in germinal center regions, produce bioactive TGF-␤1 (10). Recently, it was demonstrated that dendritic cells can promote class switching of naive CD40-triggered human B cells to an IgA phenotype in the presence of IL-10, and that this process is partially dependent on endogenous TGF-␤1 (67). It is has also been reported that TGF-␤1 may cause apoptosis in human B cells isolated from tonsil, preparations that contain germinal center B cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen-derived components and/or proinflammatory stimuli induce DCs to mature and migrate into lymphoid tissue or lymph nodes (LNs) where, as interdigitating DCs, they form a network in the parafollicular T cell-rich areas and orchestrate immune responses. Increasing evidence indicates how DCs and B cells also communicate with each other to encourage potent Th1 immunity (5)(6)(7)(8)(9)(10)(11)(12). Strategies that boost DC and B cell functions should improve prophylactic and therapeutic vaccines against pathogens like HIV.…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…We have not, to this point, characterized the ability of fully matured pDCs to stimulate B cells. Nonetheless, the observation that inclusion of pIL-4 (which did enhance APC maturity compared with pGM- (9)(10)(11)(12). In in vivo experiments conducted in the rat, DCs were observed to acquire antigen in the spleen, retain it for at least 48 h in a native form, and present it to B cells along with signals involved in isotype switching to antigen-specific B cells via direct contact (13).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions, which include T-cell-derived cytokines and the ligation of CD40 on B cells by its ligand CD154 on T cells, represent the indirect effects of mature APCs on humoral immunity (7,8). In addition, however, a more direct dialogue between DCs and B cells exists (9)(10)(11)(12)(13). Studies have provided evidence that DCs can directly stimulate the proliferation and differentiation of B cells in combination with other stimuli (9)(10)(11), and can activate naive B cells to initiate the synthesis and class-switching of antibodies (12,13).…”
Section: Introductionmentioning
confidence: 99%